Geochemical, Mineralogical, and Lithofacies Characterizations of Lacustrine Shale: A Case Study From the Cangdong Sag, Bohai Bay Basin, China - Zhao, Xianzheng; Pu, Xiugang; Zhou, Lihong; Han, Wenzhong; Xin, Bixiao; Shi, Zhannan; Tian, Jinqiang (Frontiers in Earth Science, 2021)
The study of lithofacies identification and its distribution characterizations of shales is essential for the geological evaluation of shale oil exploration and development. In this study, core description, optical microscope, total organic carbon (TOC) content, whole-rock X-ray diffraction (XRD), Rock-Eval pyrolysis, X-ray fluorescence (XRF), scanning electron microscope (SEM), and well logging data were used in the qualitative analyses of the geochemical and mineralogical characteristics of shales. Since the work of detailed lithofacies identification is still lacking in the previous studies, based on TOC, sedimentary structure, and ternary diagram of siliceous minerals, carbonate minerals, and clay minerals, eight predominant lithofacies were identified in the shale of the second member of the Kongdian Formation (Ek2): ① low to moderate organic matter content (referred to as “low to moderate TOC”) massive calcareous mudstone (C-1); ② low to moderate TOC laminated calcareous mudstone (C-2); ③ low to moderate TOC layered mixed calcareous mudstone (C-3); ④ moderate to high organic matter content (referred to as “moderate to high TOC”) laminated calcareous siliceous mudstone (S-1); ⑤ moderate to high TOC massive mixed siliceous mudstone (S-2); ⑥ moderate to high TOC laminated clayey siliceous mudstone (S-3); ⑦ low to moderate TOC massive mixed mudstone (M-1); ⑧ moderate to high TOC layered calcareous/siliceous mixed mudstone (M-2). The favorability of lithofacies was investigated based on TOC, pyrolysis parameters, pore structures, and specific mineral contents. S-1 was currently considered as the most favorable lithofacies with excellent hydrocarbon potential, high amount of free hydrocarbon, and abundant organic pores; S-2, S-3, and M-2 were considered as favorable lithofacies, while C-1 and M-1 were ranked as the least-promising lithofacies in the research area. The lateral distribution of the shale is quite different, and Ek23 contains the most favorable lithofacies for shale oil exploration.